Framing the diplomatic ties between Kazakhstan and Malaysia - Akhmet, Rakhat T.; Chew, Chee Khiang; Chang, Peng Kee (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
This study aims at investigating the prevalence news frames in the reporting of Kazakhstan President Nursultan Nazarbayev’s official visit to Malaysia in April 2012. Both quantitative and qualitative content analysis are employed to explore the way Kazakhstani and Malaysian newspapers cover the event. In terms of quantitative analysis, the focus is on the five generic frames, namely, attribution of responsibility, human interest, conflict, morality and economic consequences. While the qualitative analysis is conducted to examine how’s the issue being defined, what are the possible causes of the problem identified, moral judgement made and the supply of remedies to the problem. A total of 134 units of analysis from two major Malaysian English newspapers and two major Kazakhstani newspapers, surrounding the period of the President’s two-day visit, were collected and content analysed. The results reveal that, although the occasion was mainly about boosting economic ties between Kazakhstan and Malaysia, responsibility frame was most highlighted, while economic consequences frame was placed in the last spot. Among the four newspapers, both The Star and New Strait Times were found to be significantly more interested than Sovereign Kazakhstan and Kazakhstani Truth in using the economic consequences frame. However, results of qualitative content analysis indicate that these four newspapers were sharing the same mind to portray their respective government as capable and determined in nation development.